2017
DOI: 10.5897/ajmr2017.8692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of Salmonella species from lactating cows in dairy farm of Bahir Dar Town, Ethiopia

Abstract: Salmonella is the most important disease causing bacteria in persons as well as in animals.Antimicrobial-resistant Salmonella can be transmitted from animals to humans through consumption of contaminated food and food products. Thus, this study was conducted to determine the prevalence and antimicrobial susceptibility of Salmonella species from lactating cows in dairy farms of Bahir Dar town. A cross-sectional study was conducted in Bahir Dar town from November 2012 to June 2013. Identification of Salmonella s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Likewise, similar result, a study conducted in Brazil, also showed that the most common susceptibility profile of Salmonella enterica isolated from calves was to amikacin, amoxicillin, ampicillin, ciprofloxacin, gentamicin, tetracycline, and trimethoprim+sulfamethoxazole [41]. The susceptibility of Salmonella isolates to ciprofloxacin (100%) agreed with the reports of [42]. On the other hand, all the isolates were resistant to tetracycline (100%), streptomycin (91.4%),trimetho-prim+sulfamethoxazole(74.3%),chloramphenicol(85.7%),amoxi-cillin +clavulanic (62.9%) and gentamycin (60%) reported by in Uruguay reported that the most widespread resistance was against tetracycline (87.8%), streptomycin (85.4%) and ampicillin (22%) [33].…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, similar result, a study conducted in Brazil, also showed that the most common susceptibility profile of Salmonella enterica isolated from calves was to amikacin, amoxicillin, ampicillin, ciprofloxacin, gentamicin, tetracycline, and trimethoprim+sulfamethoxazole [41]. The susceptibility of Salmonella isolates to ciprofloxacin (100%) agreed with the reports of [42]. On the other hand, all the isolates were resistant to tetracycline (100%), streptomycin (91.4%),trimetho-prim+sulfamethoxazole(74.3%),chloramphenicol(85.7%),amoxi-cillin +clavulanic (62.9%) and gentamycin (60%) reported by in Uruguay reported that the most widespread resistance was against tetracycline (87.8%), streptomycin (85.4%) and ampicillin (22%) [33].…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, similar result, a study conducted in Brazil, also showed that the most common susceptibility pro le of Salmonella enterica isolated from calves was to amikacin, amoxicillin, ampicillin, cipro oxacin, gentamicin, tetracycline, and trimethoprim + sulfamethoxazole (41). The susceptibility of Salmonella isolates to cipro oxacin (100%) agreed with the reports of (42). On the other hand, all the isolates were resistant to tetracycline (100%), streptomycin (91.4%),trimethoprim + sulfamethoxazole(74.3%),chloramphenicol(85.7%),amoxicillin + clavulanic (62.9%) and gentamycin (60%) reported by (33) in Uruguay reported that the most widespread resistance was against tetracycline (87.8%), streptomycin (85.4%) and ampicillin (22%).…”
Section: Identi Cation Of Salmonella Enterica By Using Biolog Gen Iii...supporting
confidence: 84%
“…While Senbetu ( 2014 ) and Habtamu et al ( 2018 ) from Hawassa reported a higher prevalence rate of S. enterica , 25%, and 17.8%, respectively. Among the S.enterica prevalence reports from the Amhara region, Abebe et al ( 2023 ) (Dessie and Kombolcha), Mulaw ( 2017 ), and Hailu et al ( 2015 ) (Gondor) reported 5.92%, 9.35%, and 3.24%, respectively, which is lower than the S.enterica prevalence report during the wet season.…”
Section: Discussionmentioning
confidence: 78%